Reconstructive Options for Pressure Ulcers in Pediatric Patients - Dominika Krakowczyk; Jakub Opyrchał; Tomasz Koszutski; Krzysztof Dowgierd; Łukasz Krakowczyk (MDPI AG, 2024)
Background: Pressure ulcers pose significant challenges in terms of treatment, often exhibiting a low success rate and a propensity for recurrence. Children with neurological impairments such as myelomeningocele and those with spinal injuries are particularly vulnerable to developing pressure ulcers. Despite advancements, achieving successful reconstruction remains a formidable task. Common sites prone to pressure ulcer formation include the sacral and ischial regions, as well as areas over bony prominences. Additionally, pressure ulcers attributable to medical devices facilitating ambulation are observed. While many pressure sores resolve spontaneously, conservative management may prove ineffective for some, especially in cases of stage 3 and 4 ulcers, necessitating surgical intervention. Various surgical techniques are employed for the treatment of decubitus ulcers, yet there exists no universally accepted gold standard for their management. This paper presents our institutional experience in this domain, highlighting differences in surgical approaches, treatment outcomes, complication rates, and long-term follow-up. Methods: This study involved a retrospective analysis of medical records from 11 children, ranging in age from 10 to 17 years, who presented with extensive pressure ulcers that were unresponsive to conservative treatment measures. Data collection spanned from February 2017 to June 2022. The pressure ulcers affected various anatomical regions, including the ischial area (5/11 patients), sacral region (3/11 patients), lower limb (1/11 patients), elbow (1/11 patients), and perineal area (1/11 patients). Surgical intervention was the chosen approach for all cases, employing techniques such as reconstructive surgery utilizing perforator, pediculated flaps, and locoregional flaps. Results: Eleven patients with sore ulcers (stage 3 and 4) were treated surgically. We present our experience of using surgical methods, including pedicled anterolateral flaps, pedicled gracilis musculocutaneous flaps, propeller flaps and locoregional flaps. In some cases, surgery was performed after 60 days of hospitalization or ten years after ulcer occurrence. We reviewed the length of hospital stay, surgical management and patient satisfaction. Patients were followed up to 5 years post-surgery. All flaps survived except for one flap where partial necrosis was observed. The recurrence rate was 9.01% (1/11). One patient underwent another surgery. The general outcome was satisfactory. Conclusions: Conclusions: Our findings underscore the efficacy of flap reconstruction surgical techniques in the management of pressure ulcers among pediatric patients. Based on our experience and the outcomes observed, we advocate for considering reconstructive surgery as a viable therapeutic option early in the treatment course, particularly for stage 3 and 4 ulcers. This approach not only addresses the immediate needs of patients but also holds promise for long-term wound healing and prevention of recurrence.